Clinical pharmacology of analgosedatives in neonates: ways to improve their safe and effective use - Smits, Anne (J Pharm Pharmacol, 2016)
OBJECTIVES: To propose approaches tailored to the specific needs of neonates, such as structured product development programmes, with the ultimate goal to improve the safe and effective use of analgosedatives in these fragile patients. KEY FINDINGS: The feasibility and relevance of a structured product development programme in neonates (optimal study design based on preliminary data; model development; internal, external and prospective evaluation; an individualized dosing regimen; long-term safety; pharmacogenetics) are illustrated for the use of morphine. Based on changes in clinical practices, similar development plans are in progress for short-acting analgosedatives such as propofol, but are in need of tailored pharmacodynamic tools to assess and quantify effects. Furthermore, for drugs like paracetamol where there is already sufficient clinical pharmacology knowledge, attention needs to be given to long-term safety aspects. Finally, new covariates such as pharmacogenetics might further improve neonatal pain management, but clearly need to be integrated with other well-established covariates like age or weight. SUMMARY: Product development programmes for analgosedatives in neonates are needed. These programmes should be tailored to their specific needs (short-acting sedation, pain relief), should include long-term safety and should incorporate the exploration of newer covariates like pharmacogenetics.